The Qur'anic Epic in Iranian Cinema (Farsi) - Pak-Shiraz, Nacim (The journal of religion and film, 2016)
The representation of religious figures in Islam has become particularly controversial in recent years. The creation of religious films has, therefore, turned into a highly sensitive undertaking. Iranian cinema is one of the very few in the Muslim world to have employed this new medium in imagining and narrating stories of revered religious figures. In this article I examine the complex socio-political context of Iran to study the relatively late emergence of the epic genre in Iranian cinema. I then study the recent creation and development of "Qur’anic Films" within Iranian cinema with specific reference to Kingdom of Solomon (Mulk-i Sulayman-i Nabi, Shahriar Bahrani, 2010), which I argue is the first Qur’anic epic in Iranian cinema if not in the Muslim world. The article also draws from the Iranian television series Imam Ali (Davud Mirbaqeri, 1997) in examining the ways in which Iranian filmmakers negotiate the balance between religious authenticity and dramatic effectiveness.